(untitled) (International Seven Journal of Health Research, 2023)
Introduction: The thyroid gland produces the thyroid hormones triiodothyronine (T3) and thyroxine (T4), which regulate metabolism through the transcription of certain genes. Hypothyroidism is characterized by a decrease in the body’s metabolic activity due to the low production of important agents for this process, which can cause dyslipidemia. Objective: To analyze the association between hypothyroidism and lipid panel in biological samples from patients treated in a private laboratory in the city of Jacutinga – MG during the year 2022. Material and Method: Data from laboratory reports were collected from patients over 18 years of age who simultaneously carried out TSH, free T4, total cholesterol, HDL-c, LDL-c, VLDL-c and triglycerides tests, and after collected, the data were separated according to the presence or absence of hypothyroidism, based on the reference values for this purpose. The lipid panel of patients with hypothyroidism was also analyzed following reference values. The study variables were age and gender. Results: The study included 470 laboratory reports, where 17.66% were characterized with hypothyroidism and of these, 61.45% were female with a mean age of 51 years and 38.55% were male with a mean age 55 years old. The Total Cholesterol test and the LDL-c test showed an increase in 55,42% and 40,96% patients with hypothyroidism, respectively. Conclusion: it is concluded that females have a higher incidence of cases of hypothyroidism, especially after the age of 50. The incidence of elevated lipid tests was also higher among females.